Sparky's STEM guide to motorbikes - Holmes, Kirsty (King's Lynn, Norfolk, The Secret Book Company, 2020)
Calling all learner drivers! Meet Jeremy Sparkplug (but you can call him Sparky) and his world-class racing driver assistant, Peggy. They are your expert instructors for all things on wheels! Start your engines and watch these corners - these two will teach you everything you need to put the pedal to the metal and feel the need to speed! Learn to drive at Horses for Courses! Calling all learner drivers! Meet Jeremy Sparkplug (but you can call him Sparky) and his world-class racing driver assistant, Peggy. They are your expert instructors for all things on four (or more) wheels! Start your engines and watch those corners, they'll teach you everything you need to put the pedal to the metal and feel the need for speed! From the basics (how to go FAST) to tips and tricks (how high can a car fly?), learn all about land vehicles and earn your Golden Horseshoes! On your marks... get set... GO!